Protective effect of extracorporeal membrane oxygenation on intestinal mucosal injury after cardiopulmonary resuscitation in pigs - Liang, Yong; Li, Chunsheng; Liu, Bo; Zhang, Qiang; Yuan, Xiaoli; Zhang, Yun; Ling, Jiyang; Zhao, Lianxing (Experimental and therapeutic medicine, 2019)
The present study aimed to explore the protective effects of extracorporeal membrane oxygenation (ECMO) on intestinal mucosal injury following cardiopulmonary resuscitation (CPR), and to assess the potential mechanisms involved. A total of 24 healthy adult domestic pigs were selected as the study subjects. A ventricular fibrillation model was induced through programmed electric stimulation. Subsequently, the animals were randomly divided into conventional CPR and CPR+ECMO groups (n=12 per group). The mortality and hemodynamic parameters of the two groups were compared. The expression levels of inflammatory cytokines in the serum and intestinal mucosa were detected by ELISAs. The intestinal mucosa was subjected to hematoxylin and eosin, and immunohistochemical staining, followed by electron microscopy, to assess the degree of apoptosis and necrosis. The animals in both groups recovered from the programmed ventricular fibrillation. In the CPR group, two animals died at 2 h and two more animals died a further 2 h later, resulting in a 33.3% mortality rate, whereas no cases of mortality were observed in the CPR+ECMO group. Compared with the animals in the CPR group, the hemodynamic parameters of the animals in the CPR+ECMO group revealed significantly improved outcomes. Multiple inflammatory factors (tumor necrosis factor [alpha], interleukin-1 and interleukin-6), myeloperoxidase and malondialdehyde levels were decreased, whereas Na/Ca-ATPase and superoxide dismutase levels were elevated in the intestinal mucosa of animals in the CPR+ECMO group compared with those in the CPR group. Additionally, pathological staining demonstrated that the intestinal mucosa tissue in the CPR+ECMO group exhibited less apoptosis, necrosis and inflammatory cell infiltration, which was further supported by a decrease in Bax expression and an increase in Bcl-2 expression. Overall, ECMO after CPR reduced the intestinal mucosal barrier injury after spontaneous circulation recovery, and the mechanism involved decreased inflammation and apoptosis. Key words: cardiac arrest, cardiopulmonary resuscitation, intestinal mucosal barrier, extracorporeal membrane oxygenation